Understanding the Hydro‐Metathesis Reaction of 1‐Decene By Using Well‐Defined Silica Supported W, Mo, Ta Carbene/Carbyne Complexes. Issue 8 (22nd February 2018) - Saidi, Aya; Samantaray, Manoja K.; Tretiakov, Mykyta; Kavitake, Santosh; Basset, Jean‐Marie
Abstract: Direct conversion of 1‐decene to petroleum range alkanes was obtained using hydro‐metathesis reaction. To understand this reaction we employed three different well‐defined single site catalysts precursors; [(≡Si‐ O ‐)W(CH3 )5 ]1, [(≡Si‐ O ‐)Mo(≡C t Bu)(CH2 t Bu)2 ]2 and [(≡Si‐O)Ta(=CH t Bu)(CH2 t Bu)2 ]3 . We witnessed that in our conditions olefin metathesis/isomerization of 1‐decene occurs much faster followed by reduction of the newly formed olefins rather than reduction of the 1‐decene to decane, followed by metathesis of decane. We found that Mo‐based catalyst favors [2+2] cycloaddition of 1‐decene forming metallocarbene, followed by reduction of the newly formed olefins to alkanes. However, in the case of W and Ta‐based catalysts, a rapid isomerization (migration) of the double bond followed by olefin metathesis and reduction of the newly formed olefins were observed. We witnessed that silica supported W catalyst precursor1 and Mo catalyst precursor2 are better catalysts for hydro‐metathesis reaction with TONs of 818 and 808 than Ta‐based catalyst3 (TON of 334). This comparison of the catalysts provides us a better understanding that, if a catalyst is efficient in olefin metathesis reaction it would be a better catalyst for hydro‐metathesis reaction. Abstract : Hydro‐Metathesis : Direct conversion of 1‐decene to petroleum range alkanes was obtained using hydro‐metathesis reaction. To understand this reaction three different well‐defined single site catalysts precursors were employed.